Novel Antioxidants and α-Glycosidase and Protein Tyrosine Phosphatase 1B Inhibitors from an Endophytic Fungus Penicillium brefeldianum F4a - Yan Bai; Ping Yi; Songya Zhang; Jiangchun Hu; Huaqi Pan (Journal of Fungi, 2021)
Oxidative stress plays a very important role in the progression of diabetes and its complications. A therapeutic agent that is both antidiabetic and antioxidant would be the preferred choice for the treatment of diabetes. The crude extract of the endophytic fungus Penicillium brefeldianum F4a has significant antioxidant and α-glycosidase and protein tyrosine phosphatase 1B (PTP1B) inhibition activities. Chemical investigation of P. brefeldianum F4a using an activity-guided isolation led to the discovery of three new compounds called peniorcinols A–C (1–3) along with six known compounds: penialidins A (4), penialidin F (5), myxotrichin C (6), riboflavin (7), indole-3-acetic acid (8), and 2-(4-hydroxy-2-methoxy-6-methylphenyl) acetic acid (9). Their chemical structures were established by their NMR and HRESIMS. The absolute configurations of 1 and 3 were determined by experimental and calculated electronic circular dichroism (ECD). Their antioxidant activities were evaluated by DPPH• and ABTS•+ scavenging assays. Compounds 1–6 and 8–9 showed moderate to strong free radical scavenging activities. Significantly, 4–6 exhibited more potent ABTS•+ scavenging activity than that of the positive control. Their α-glycosidase and PTP1B inhibition activities were tested. Among them, compound 3 showed α-glucosidase inhibition activity, and compounds 7 and 8 showed PTP1B inhibitory activity for the first time. It is worth noting that 3 and 8 displayed both antioxidant and α-glycosidase or PTP1B inhibition activities. These finding suggest that compounds 3 and 8 could be used as lead compounds to generate new potent drugs for the treatment of oxidative stress-related diabetes.